Pengaruh Bentuk Pakan (Crumble Dan Pellet) Terhadap Pertumbuhan, Berat Karkas Dan Profil Saluran Pencernaan Ayam Broiler - Rosalinda Kristanti Intan Tahu; Frans U Datta; Heny Nitbani (Program Studi Kedokteran Hewan, Universitas Nusa Cendana, 2022)
This research is an experimental type of research that uses the RAL method (Completely Randomized Design) with two treatments, namely complete feed in the form of granules (crumbles) and complete feed in the form of pellets (pellets). Each treatment used 35 broiler chickens aged 2 weeks. This study aimed to examine the effect of feed form (crumble and pellet) on growth, carcass weight and digestive tract profile of broiler chickens in the grower to finisher period. From the first day until the age of 12 days (starter period) chicks (DOC) were given complete feed in the form of crumbs. The research data were analyzed by Independent T test using SPSS. The results of data analysis showed that there was a significant effect of treatment (P<0.05) on proventriculus weight and no significant effect (P>0.05) on body weight, carcass weight, ventriculus weight, and weight and length of the small intestine of broiler chickens. It can be concluded that statistically, in the grower period, feed particle size had little effect on growth and carcass weight and digestive tract profile. However, empirically, the carcass weight of the granular group (807 g) versus the pellet group (858 g) was quite different so that economically, giving complete feed in the form of pellets was more profitable.